Answer:
As x→[infinity], f(x)→[infinity] As x→−[infinity], f(x)→−[infinity]
Explanation:
Since f(x) =2x³/3,
Let x → + ∞
Substituting x = + ∞ into the equation, we have
f(+∞) = 2(+∞)³/3
= + 2∞³/3
= + ∞ (since + 2∞³/3 → +∞ (a larger number))
So as x → + ∞, f(x) → + ∞
Let x → - ∞
Substituting x = - ∞ into the equation, we have
f(-∞) = 2(-∞)³/3
= - 2∞³/3
= - ∞ (since - 2∞³/3 → -∞ (a larger number))
So as x → -∞, f(x) → -∞
So, the answer is As x→[infinity], f(x)→[infinity] As x→−[infinity], f(x)→−[infinity]